Relevansi Agama dalam Era Sains Modern: Sebuah Refleksi Epistemologis - Demila Siti Padilah (Gunung Djati Conference Series, 2023)
This study aims to discuss the relevance of religion in the era of modern science. This study uses research methods with library studies. Relevance theory occupies a position as a formal object. Meanwhile, modern religion and science become material objects. The results and discussion in this study are that science and religion mutually complement and reinforce each other, but still maintain their respective existences. For example, the benefits of the month of Ramadan for health are explained by dietary principles from medical science. This form seems to validate each other between science and religion. The thing that makes religion and science incompatible in modern times is because there are anomalies in science. For example, positivistic, which means they only believe everything that has facts and everything that makes sense. This study recommends institutions and organizations that have close links with religion or science to conduct studies on religion and science.